Mitigating Cross-Species Viral Infections in Xenotransplantation: Progress, Strategies, and Clinical Outlook - Yenong Zhou; Shuyu Zhou; Qian Wang; Bing Zhang (Cell Transplantation, 2024)
Xenotransplantation holds great promise as a solution to address the critical shortage of organs, but it raises concerns regarding the potential transmission of porcine viruses to recipients, leading to infections and even zoonotic diseases. Data used in this review were mainly from literature of Pubmed database. Keywords included xenotransplantation, infection, virus, and epidemiology. The original articles and critical reviews selected were relevant to this review’s theme. We review the major viral infections of concern in xenotransplantation, their risk of transmission, diagnosis, treatment, and ways to prevent infection. Then, we pivot to a comprehensive overview of the current status of xenotransplantation. In addition, we offer our own insights and recommendations for propelling xenotransplantation forward, transitioning from preclinical experiments to the critical phase of clinical trials. Viral infections pose considerable safety concerns within xenotransplantation, particularly with the possibility of emerging or currently unidentified viruses. Clinical trials serve as a crucial platform to progress the safety standards of xenotransplantation. However, further studies and dedicated efforts are required to effectively translate findings into practical applications that can improve safety measures in this field.